Pengaruh Pelatihan dan Pengembangan terhadap Kinerja Karyawan - Nurzaman, Adnan; Gunawan, Ahmad (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This article was prepared based on the results of previous research regarding the impact of training on employee performance. with the aim of understanding the effect of job training on employee performance at these companies. This article was written using the library study method. The purpose of this article is to assess whether job training has a significant influence on employee performance in a company. Along with various previous research results that show inconsistencies in the impact of job training and development on companies, this topic is still interesting for further research. Human resource management in a company must be carried out professionally to achieve a balance between employee needs and organizational demands and capabilities. The importance of human resource management can be realized because the success of all organizational activities in achieving its goals is very dependent on the ability of the human resources who manage the organization. Employees need to be managed well in order to make sufficient contributions to achieve the goals set by the company.